A novel host defense system of airways is defective in cystic fibrosis - Moskwa, Patryk; Lorentzen, Daniel; Excoffon, Katherine J D A; Zabner, Joseph; McCray, Jr, Paul B; Nauseef, William M; Dupuy, Corinne; Bánfi, Botond (American journal of respiratory and critical care medicine, 2007)
The respiratory tract is constantly exposed to airborne microorganisms. Nevertheless, normal airways remain sterile without recruiting phagocytes. This innate immune activity has been attributed to mucociliary clearance and antimicrobial polypeptides of airway surface liquid. Defective airway immunity characterizes cystic fibrosis (CF), a disease caused by mutations in the CF transmembrane conductance regulator, a chloride channel. The pathophysiology of defective immunity in CF remains to be elucidated. We investigated the ability of non-CF and CF airway epithelia to kill bacteria through the generation of reactive oxygen species (ROS). ROS production and ROS-mediated bactericidal activity were determined on the apical surfaces of human and rat airway epithelia and on cow tracheal explants. Dual oxidase enzyme of airway epithelial cells generated sufficient H(2)O(2) to support production of bactericidal hypothiocyanite (OSCN(-)) in the presence of airway surface liquid components lactoperoxidase and thiocyanate (SCN(-)). This OSCN(-) formation eliminated Staphylococcus aureus and Pseudomonas aeruginosa on airway mucosal surfaces, whereas it was nontoxic to the host. In contrast to normal epithelia, CF epithelia failed to secrete SCN(-), thereby rendering the oxidative antimicrobial system inactive. These data indicate a novel innate defense mechanism of airways that kills bacteria via ROS and suggest a new cellular and molecular basis for defective airway immunity in CF.